Characterization of the political system in colombia. Instable structure, restrictive/stable process and poor political results [Caracterización del sistema político colombiano. Estructura inestable, proceso restrictivo/estable y resultados políticos bajos] (2018)
In this article, a characterization of the political system in Colombia is presented, based on three political dimensions (structure, process and political result), with the purpose of showing that the creation of the Colombian state plays a decisive role in the configuration and performance of its political regime. Although it is argued that this regime is and has been democratic during most part of its existence, a significant paradox can be found inside the system: The presence of an unstable political structure, a restrictive political process and low levels of satisfaction in fundamental functions of the State, but even so, it can be considered a stable political system, comparatively speaking. © 2018, Universidad del Zulia. All rights reserved.